Effects of Cornus walteri extract on hepatic lipid-regulating enzyme activities in high fat diet-induced obese rats - Yun, Sung Ho; Lee, Joonsoo; Suh, Hyung Joo; Jung, Eun Young (Progress in Nutrition, 2018)
In this study, we investigated whether the body fat suppressive effects of Cornus walteri extract (CE) were due to alterations in lipid-regulating enzyme activities in high fat diet-induced obese rats. Male Sprague-Dawley rats were randomly divided into three groups (n=6): a normal diet group (N-control), a high fat diet group (F-control), and a high fat diet group, treated orally with CE (0.25%) in their drinking water (Treatment). After five weeks, CE supplementation tended to reduce body-weight gain and visceral fat in the diet-induced obese rats. The activity of hepatic glucose-6-phosphate dehydrogenase (G6PD) and malic enzyme (ME), responsible for fatty acid synthesis, tended to be lower in the Treatment group compared to the non-treated groups. This finding indicates that the body fat suppressive effects of CE are most likely due to decreases in hepatic fatty acid synthesis. CE supplementation increased hepatic carnitine palmitoyltransferase (CPT) activity, which suggests that β-oxidation was enhanced. In conclusion, CE supplementation suppressed body fat accumulation by attenuating fatty acid synthesis and enhancing β-oxidation through alteration of lipid-regulating enzyme activities.